Surveillance and diagnostics of the emergent Sri Lankan cassava mosaic virus (Fam. Geminiviridae) in Southeast Asia - Siriwan, Wanwisa; Jiménez Polo, Jenyfer; Hemniam, Nuannapa; Saokham, Kingkan; López Alvarez, Diana; Leiva Sandoval, Ana Maria; Martínez, Andres; Mwanzia, Leroy; Becerra López Lavelle, Luis Augusto; Cuéllar, Wilmer Jose (Elsevier, 2020)
Emergent agricultural pathogens cause severe damage worldwide and their invasive potential is significantly increased by global trade, crop intensification and climate change. Standard surveillance and diagnostic protocols need to be evaluated and implemented, particularly with diseases caused by a wide range of pathogens that induce similar symptoms. Such is the case with Cassava Mosaic Disease (CMD) present in Africa and Asia, and associated with mixed virus infections and recombinant and re-assorted virus strains. CMD has been recently reported in Southeast Asia (SEA) and is already widely spread throughout this region. This communication offers an update on protocols and tools used to track the distribution of CMD and to characterize the pathogen associated with it in SEA.